EFISIENSI TEKNIS USAHATANI PISANG CAVENDISH MENGGUNAKAN STOCHASTIC FRONTIER ANALYSIS (SFA) DI KABUPATEN BOJONEGORO - Waffiq Fauziah, Saila; Yusuf Dawud, Moh.; Djohar, Noor (Universitas Islam Balitar, 2023)
This study uses stochastic frontier analysis (SFA) to evaluate the efficacy of Cavendish banana cultivation technology in Bojonegoro Regency. An opinion survey of 16 Cavendish banana farmers spread across seven sub-districts in Bojonegoro Regency provides primary data. Farmers' technical productivity and the variables that affect it are assessed using SFA analysis. Based on the findings, Cavendish banana producers in Bojonegoro Regency have an average technical productivity of 80.8%. The stochastic frontier production function model includes the seven variables shown in table 1 and hypothesized to have an impact on output levels: land area, seeds, chemical fertilizers, organic fertilizers, labor, and capital. Large areas of land, organic fertilizers and pesticides are all elements that have a significant impact on the effectiveness of farmer technology. While age, education level, and number of family members are variables that affect inefficiency. The variable level of education is an element that has quite a large influence on technological inefficiency. The findings of this study are expected to educate relevant stakeholders and increase the effectiveness of the technology for the Cavendish banana industry in Bojonegoro Regency.